Variables Influencing the Production of Door Jambs from Pinus taeda EGP Panels - Dias, Romulo R. [UNESP]; Alves, Manoel C. S. [UNESP]; Deus, Priscila R.; Vieira, Fabio H. A. (BioResources, 2023)
The influence of coverslip width and the physical arrangement of growth rings were studied relative to laterally glued Pinus taeda wood panels (EGP) used in the manufacture of door jambs, according to the requirements of ABNT-NBR 15.930 (2011). The goal was to determine the combination providing the best physical performance of the product. The experiments used the complete factorial design for two factors and four levels, i.e., 32, 56, 75, and 112 mm width coverslips, and rings arrangement of radial, tangential, cross coverslips, and ones with finger joints. A total of 48 EGP door jamb specimens (3 for each combination) measuring 2120 x 220 x 32 mm, with moisture content between 8% and 12% and apparent density between 400 and 600 kg.m-3 were used. Statistical analysis of variance (ANOVA) was used to investigate the influence of factors and their interactions on the following responses: visual aspect, moisture, density and dimensional (width and thickness) variations. It was found that both factors and their interactions influenced the level of significance of 1% on shape deviations. The best results were for panels produced with 32 and 56 mm coverslips, with cross or radial arrangement.
Keywords: EGP; Growth rings; Pine wood